Human Factors Practice in Malaysia: Professional Liability, Accountability and Ethics - Rabiul, Ahasan (2014)
In Malaysia, practicing human factors and ergonomics (http// jobs.gecareers.com/keythuman - factors- usability-job-malaysia.html) has been significantly increased to the design and improvements of all kinds of work systems. Human Factors (HFs) experts and ergonomists are employed in various companies including oil and gas industries (wwwoilandgaspeople.comfoil-and-gas-jobs-search/s/malaysia/kuala-lumpudengineering/jobs/human-factors-engineer-773722258.asp). However, it is a great challenge how these professionals contribute their skills to the design of products and systems that are ethically standard. There is also a need to ensure that the workers are safe and healthy in a productive environment. The choices of individuals practicing HFs should thus be encouraged through the concept of professional liability, accountability and ethics that tell about the best practice we must do things as an ergonomist or behave properly to be HFs expert. It is about how our practices impact our society', and how we should be liable to our work. In terms of professional accountability and liability, we are facing tremendous challenges in our profession. As HFs experts, we are practicing to deal with usability or design issues lacking behind of efficacy and transparency of our profession. Our job is not only the design of job-tasks and maximizes work efficiency. Liability and trust issues in our profession means how we maintain us, how we recognize and treat us, how we ethically behave as a professional through the quality of our work, not the quantity of our work Hence, our professionalism is question and perhaps critical in the way we do things. HFs as the subject of our profession focuses interactions amongst people, tasks, or system environment (Figure O. It is often viewed as workplace health, safety and ergonomics with its own specific research methods 11,21 to improve productivity, efficiency, wellbeing and quality of life. in the coming days, HFs continues to be a major issue for industries and companies as a key element of improving usability and issues. And, therefore, our abilities to proper use of HFs expertise need clarification in terms professional accountability, liability and ethics.